Current State of Method Development for PCR Sample Peparations - M. S. Tikhvinskiy; A. A. Vorobiov; Ya. A. Kibirev; G. S. Usenko; A. I. Kozlov; S. G. Isupov (Вестник войск РХБ защиты, 2021)
The sensitivity, specificity and reproducibility of molecular genetic methods of analysis largely depend on the quality of the preliminary preparation of the analyzed samples. During the sample preparation, the tasks of disinfecting pathogenic material, lysing cell membranes, removing compounds and impurities that inhibit the polymerase chain reaction (PCR), as well as concentrating nucleic acids are solved. The purpose of this work is to select modern approaches to sample preparation for the PCR. Among the variety of different methods of sample preparation, the most widespread are the methods based on chemical lysis of cell membranes using chaotropic compounds, followed by purification of nucleic acids by solid-phase extraction using magnetic particles. This approach is implemented both in commercial kits for manual sample preparation and in various automated systems for the isolation of nucleic acids. The analysis of commercially available stations for the isolation of nucleic acids shows that their technical characteristics are similar: the duration of one isolation cycle is 40–90 minutes; the volume of the analyzed samples is from 0.1 to 2.0 ml; the number of simultaneously processed samples max – 96, min – 8. The method of the nucleic acid isolation is the magnetic particles. The main differences are in the type of analyzed samples, and technologies for lysis of the test material and DNA extraction. Our experience in the use of magnetic particle kits for the isolation of nucleic acids, both in stationary and in field laboratories confirms the effectiveness and reliability of this technology. Further development and improvement of the hardware for such work will, obviously, be aimed at miniaturizing the equipment, developing field portable automatic nucleic acid extraction stations, as well as integrating the process of sample preparation and analysis by PCR in one device.